Microbiota–liver axis and host transcriptomic mechanisms underlying the anti-obesity effects of Bifidobacterium animalis DPU-MWFBA in early-life overfeeding - Zhongyang Gao; Baoyuan Zhao; Guangqing Mu; Hui Nie; Xiaomeng Wu (Food Microbiology, 2026)

Multiple magma sources and incremental assembly of the late Mesozoic Yunmengshan batholith, North China Craton: Constraints from zircon Hf-O isotopes and apatite geochemistry - Zi-Mu Li; Miao-Miao Ling-Hu; Shi Chen; Jin-Feng Sun; Ji-Heng Zhang; Ya-Dong Wu; Bao-Quan Zhou; Quan-Lin Hou; Jin-Hui Yang (Lithos, 2026)

Bioinspired fibrous electronic sensor for pressure and temperature monitoring with passive thermal regulation - Qinghua Liu; Leihuan Mu; Hui Liu; Jiehui Li; Ruizhe Zhang; Jinmei He; Lei Zhu; Mengnan Qu (Chemical Engineering Journal, 2026)

WDS-Modality: A Physics-Informed Multi-Modal Agent Framework for Resilient Water Distribution System Assessment Using Large Language Models without Fine-tuning - Tianwei Mu; Yue Wang; Manhong Huang; Mingzhe Yuan; Dan Xue; Wenhong Wang; Hui Yang; Jun Li; Bo Zhou (Water Research, 2026)

Supplemental vitamins A, D, and E improve OPU-IVP efficiency in postpartum dairy cows by alleviating oxidative stress - Jinbang Xiao; Manyuan Tian; Zhengjie Ding; Haohao Mu; Haitao She; Heqiang Li; Bingke Wang; Hui Chen; Yonghong Jia; Yongsheng Wang; Yaping Jin; Pengfei Lin (Theriogenology, 2026)

Systematic review of naturally occurring benzylisoquinoline alkaloids (2015–2024): phytochemistry, bioactivity and structure-activity relationship - Jing Liu; Tao Liu; Mu-Yan Liu; Hui-Hui Li; Xiao-Yu Zhao; Hui Zhang; Yan Ge; Ze-Dong Nan (Phytochemistry, 2026)

Deciphering mechanisms of environmental adaptation, antibiotic tolerance, and potential virulence traits of Pseudomonas baetica isolated from anthropogenic habitat - Mu-Qi Zhang; Yi-Cheng Wang; Ming-Ying Mao; Yin-Qiu Qin; Peng Yan; Hui-Min Fu; Yuan-Xiang Mao; Ji-Cheng Liu; You-Peng Chen; Meng-Jiao Gao (Journal of Environmental Chemical Engineering, 2026)

Household fuel types and nonfatal cardiovascular diseases in middle-aged and elderly adults - Ruirui Ma; Yingjun Mu; Qingyao Wang; Junyao Huang; Jiayao Zhu; Xudong Wang; Min Zhou; Hui Zuo (Environmental Pollution, 2026)

Effects of fine particle migration caused by one wetting-drying cycle on desiccation micro-cracks in intact loess - Zhi-yuan He; Peng-hui Ma; Qing-yi Mu; Chao Zhou; Ke Mu; Zhi-jie Jia; Jian-bing Peng (Engineering Geology, 2026)

Preparation and evaluation of silicate stabilized FeS nanoslurry for in-situ remediation of hexavalent chromium - Ning-Ning Xing; Hong-Ling Zhang; Pan-Pan Mu; Hui Jiang; Hong-Bin Xu (Chemical Engineering Journal, 2026)

Transformation of selenium fractions driven by freeze-thaw cycles in two soils: Soil aggregate reconstruction and microbial community response - Mengqin Ren; Jiacheng Wu; Yumeng Liu; Lei Pan; Haotian Gong; Yuxin Mu; Min Wang; Hui Zhai (Environmental Research, 2026)

TME-activated MXene nanoheterojunctions engineer cancer cells through phototherapy and metabolic interference for enhanced cuproptosis and immunotherapy - Hui Li; Jie Geng; Min Mu; Susu Xiao; Chenqian Feng; Lihua Zhou; Yuanxiang Wang; Wei Yu; Rangrang Fan; Bo Han; Gang Guo (Chemical Engineering Journal, 2026)

GnRH supplementation in the PreOvsynch protocol targeting follicular cysts enhances synchronization and reduces days open in dairy cows - Jinbang Xiao; Manyuan Tian; Zhengjie Ding; Haohao Mu; Haitao She; Heqiang Li; Bingke Wang; Hui Chen; Yonghong Jia; Yongsheng Wang; Yaping Jin; Pengfei Lin (Animal Reproduction Science, 2026)

Scale-Up performance and high-cell-density operation of a three-stage PHA biorefinery using liquor-making wastewater - Qingxin Liu; Menghan Wu; Yandong Xie; Jiayu Liu; Mengsha Mu; Peng Yu; Hui Wang (Water Research, 2026)

External electronic effect enhances room-temperature phosphorescence and photochromism in organophosphine oxide - Zhuke Gong; Xiudan Song; Jianhui Sun; Ruotong Ma; Qingfeng Mu; Yuanting Guo; Xiaojun Zhang; Hui Xu (Science Bulletin, 2026)

Water droplets in crude oil: A new window into microbiome and microbial activity in subsurface oil reservoirs - Qiao-Hui Wang; Yi-Fan Liu; Lei Zhou; Shi-Zhong Yang; Ji-Dong Gu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2026)

Impact of Fly Ash on the CO2 Mineralization Efficiency and Interfacial Transition Zone Properties of Sustainable Coal Gangue-based Materials - Lei Qin; Feilong Zhang; Zitong Xue; Hui Wang; Miao Mu; Meiling Xiong; Niandong Chen (Water, Air, & Soil Pollution, 2026)

Effects of Dietary Macleaya cordata Extract on Growth Performance, Antioxidant Capacity, Immunity, and Stress Resistance in Juvenile Red Claw Crayfish (Cherax quadricarinatus) - Fan-Le Jia; Yao-Peng Lu; Ze-Long Zhang; Xiu-Xia Zhang; Pei-Hua Zheng; Jun-Tao Li; Ying-Hui Liang; Dan Mu; Jian-An Xian (Fishes, 2026)
High-density, intensive aquaculture has led to the deterioration of the aquatic environment, which compromises the survival, immune function and disease resistance of aquatic animals. This study investigated the effects of dietary supplementation with different levels of Macleaya cordata extract (MCE) on growth performance, muscle composition, antioxidant capacity, immune function, and stress resistance in red claw crayfish (Cherax quadricarinatus). Juvenile crayfish with an initial body weight of 0.22 ± 0.02 g were fed diets supplemented with 0 (Diet 1, Control), 0.01 (Diet 2), 0.02 (Diet 3), 0.04 (Diet 4), 0.08 (Diet 5), and 0.15 (Diet 6) g/kg MCE for eight weeks. Results showed that dietary MCE supplementation had no significant effect on the growth performance or muscle composition of crayfish. Conversely, supplementation with 0.02–0.04 g/kg MCE significantly increased the activities of superoxide dismutase (SOD), glutathione peroxidase (GPx), phenoloxidase (PO), and the total antioxidant capacity (T-AOC) in the hepatopancreas and plasma, while significantly reducing malondialdehyde (MDA) levels. Specifically, supplementation with 0.04 g/kg MCE significantly upregulated the hepatopancreatic mRNA expression levels of SOD, hemocyanin, GPx, and selenium-dependent glutathione peroxidase (Se-GPx). Furthermore, the challenge test demonstrated that supplementation with 0.04 g/kg MCE significantly improved crayfish survival under microcystin-LR (MC-LR) stress. Overall, supplementation with 0.04 g/kg MCE significantly improved the antioxidant capacity, immunity, and stress resistance of crayfish, suggesting its potential as an environmentally friendly immunostimulatory feed additive to protect against MC-LR stress in crayfish.

Integrating network pharmacology, molecular dynamics, and in vitro assays to unveil the mechanism of costunolide against gastric cancer - Chaohong Zhu; Qiuxiong Chen; Ying Li; Hui Wu; Qijun Ming; Mengyue Ma; Junjie Mu; Xiaoqin Long; Xian Yang; Xue Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Sulfur vacancy-rich MoS2 nanoflowers as electron shuttles boost Fe(VI) activation for efficient micropollutant degradation - Lian Wu; Xin Zhou; Zi-Yi Han; Hui-Zhi Mu; Lu Wang; Yu-Lei Liu; Jun Ma (Journal of Hazardous Materials, 2026)

WITHDRAWN: Corrigendum to "H2S-releasing versatile hydrogel dressing with potent antimicrobial, anti-inflammatory, epithelialization and angiogenic capabilities for diabetic wound healing" [Chem. Eng. J. 469 (2023) 143398] - Jiale Chen; Zhixiang Mu; Dongfan Chen; Chen Huang; Ting Jin; Lin Li; Youyun Zeng; Qiang Zhou; Yanmei Zhang; Hongli Mao; Hui Deng; Xinkun Shen; et al. (Chemical Engineering Journal, 2026)

Tidal level seasonally modulates sediment organic carbon in seagrass meadows of tropical lagoon bays - Xiao-Ya Zhang; Hui-Jue Luo; Qian-Wei Li; Mu-Qiu Zhao; Zhen Ni; Yun-Feng Shi; Yin-Liu Wang; Yu-Chao Li (CATENA, 2026)

Genome-wide association analysis and candidate gene identification for plant height in Shanxi local foxtail millet varieties - Wei Zhou; Huibin Qin; Haigang Wang; Hui Zhi; Rui Huang; Sen Hou; Junjie Wang; Ling Chen; Xiang Tian; Zhijun Qiao; Zhixin Mu; Xianmin Diao (Theoretical and Applied Genetics, 2026)

Antibacterial mechanism of combined high-voltage electrostatic field and low-temperature energy field against Bacillus cereus in milk sources - Zhaobin Yan; Guibing Pang; Zhao Zhang; Xiaomeng Wu; Guangqing Mu; Hui Zhang (Innovative Food Science & Emerging Technologies, 2026)

Data driven analysis on changing patterns of reactive nitrogen deposition in East and Southeast Asia - Jiani Tan; Yan Zhang; Xuejun Liu; Yun Fat LAM; Mohd Talib Latif; Kasemsan Manomaiphiboon; Joshua S. Fu; Maggie Chel Gee Ooi; Ling Huang; Yangjun Wang; Hui Chen; Kun Zhang; et al. (Atmospheric Environment, 2026)

Plasma Tryptophan Hydroxylase 1 Activity-related Metabolic Markers and Stroke Risk: A Nested Case–control Study - Yingjun Mu; Ruirui Ma; Qingyao Wang; Xudong Wang; Shujun Gu; Hui Zuo (Translational Stroke Research, 2026)

Modulating soil enzyme functions: The role of aggregate structure in arsenic-contaminated soils under dry-flood cycle - Hui Huang; Ziquan Wang; Peimei Guan; Rongyu Mu; Chuanyou Wang; Mallavarapu Megharaj; Haixia Tian; Wenxiang He (Applied Soil Ecology, 2026)

Two undescribed benzofuran derivatives from chaetomium elatum - Chen-Yi Yan; Feng Ju; Yu-Hui Chen; Yu-Ting Mu; Yun-Jie Hu; Da-Le Guo; Yun Deng; Qi-Xuan Kuang (Natural Product Research, 2026)

The effect of high-voltage electrostatic field combined with low-temperature hybrid energy field on the protein structure and antioxidant properties of pasteurised milk - Zhaobin Yan; Hui Zhang; Zhao Zhang; Xiaomeng Wu; Guangqing Mu; Guibing Pang (Innovative Food Science & Emerging Technologies, 2026)

The role of the marine new infrastructure in the low-carbon development of marine fisheries--micro-level evidence from China - Li Zhang; Hui Zheng; Ning Yu; Hairong Mu (Ocean & Coastal Management, 2026)

DlNAC41 and DlNAC100 transcription factors modulate longan pulp breakdown via adjusting the expression of cell wall degradation-related genes - Hui Wang; Wenlong Zhou; Xinyue Mu; Zhongqi Fan; Ruiling Zhuo; Yihui Chen; Wangjin Lu; Boqiang Li; Shiping Tian; Yifen Lin; Hetong Lin (Postharvest Biology and Technology, 2026)

Ailancoumaquinone A and ailancoumarins M-T, undescribed terpenylated coumarins from Ailanthus altissima and their anti-inflammatory activity - Da-Le Guo; Li Huang; Hui-Min Zhang; Yu-Ting Mu; Hao-Ran Lei; Li-Lian Zhao; Su Hu; Yun-Jie Hu; Cong-Cong Li; Meng-Dan Liu; Yu-Cheng Gu; Guan-Kui Yang; et al. (Phytochemistry, 2026)

Environmental standard limit fluoride exposure prioritizes neurotoxicity over osteotoxicity in larval zebrafish: A benchmark dose analysis - Xiumei Yang; Xianmei Zhang; Guojun Jian; Yuanhui Zhu; Hangyu Chen; Xiaoxi Mu; Jie Li; Bijin Zhu; Hui Lu; Yan An; Tingxu Jin (Aquatic Toxicology, 2026)

Metabolic coupling of arsenic, carbon, nitrogen, sulfur and iron in high-salinity groundwater in the Yellow River Delta: Insights from metagenomic analyses - Chuanshun Zhi; Dahai Wang; Baonan He; Guohua Hou; Maosheng Gao; Hui Mu; Ruchun Wei; Xiancang Wu; Jing Bai; Yufei Jiao; Xiaonong Hu (Water Research, 2026)

A flexible methanol production process scheduled by carbon price fluctuation: Techno-economic and risk analysis - Jincheng Pan; Jiusheng Mu; Jing Ding; Chundong Zhang; Hui Wan; Guofeng Guan (Journal of Cleaner Production, 2026)

Enhancement of calcium oxide on hydrogen production and degradation of polylactic acid microplastics in anaerobic fermentation - Xiaoxuan Zhu; Ruirui Shang; Xi Yang; Chuanzheng Song; Hui Mu; Chunhui Zhao; Huanhuan Guo; Yongfang Zhang (Journal of Environmental Management, 2026)

Amorphous phosphate-mediated Schottky junction at Mo2N-based heterojunction interface to accelerate interfacial electron transfer for boosted photocatalytic hydrogen evolution - Yu-pei Li; Zi-xin Qi; Xiao-jing Wang; Jun Zhao; Jun Yang; Hui-ying Mu; Fa-tang Li (Chemical Engineering Journal, 2026)

Fe3O4 nanoparticles and cytochrome c synergistically facilitate lactate chain elongation to caproate - Yichao Wang; Chunhui Zhao; Fangyuan Feng; Yaomin Xi; Wenhan Chen; Xiaoyu Zhu; Xiang Li; Chuanshun Zhi; Hui Mu (Journal of Environmental Chemical Engineering, 2026)

Recent advances in cellulose-based paper for flexible pressure sensors: A review - Qinghua Liu; Leihuan Mu; Jiehui Li; Jinmei He; Hui Liu; Menglin Zhu; Pu Feng; Xuedan Zhu; Cai-Li Sun; Mengnan Qu (Carbohydrate Polymers, 2026)

Plasma Metabolites of Kynurenine Pathway and Risk of Stroke in the General Population: A Nested Case–control Study - Yingjun Mu; Xudong Wang; Qingyao Wang; Zhenquan Lu; Zhengyuan Zhou; Shujun Gu; Hui Zuo (Translational Stroke Research, 2026)

Dehydrocostus lactone induces apoptosis and mitophagy in gastric cancer cells through the ROS-mediated mitochondrial pathway - Qiuxiong Chen; Ying Li; Junjie Mu; Qian Ming; Chaohong Zhu; Ziyue He; Mengyue Ma; Xiaoqin Long; Hui Wu; Baoli Qiu; Lihe Zhang; Xian Yang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Decoding ore-forming fluids evolution through multi-stage scheelites: Insights from the first Neoproterozoic Jianzidong W deposit in the western Yangtze, South China - Zhongyuan Liu; Fuhao Xiong; Han Zhao; Jie Gan; Junqing Mu; Yu Gan; Hui Li; Yaming Tian; Hao Zou (Lithos, 2026)

Root exudates drive metabolic remodeling of microbial and resistance to facilitate sulfonamide biodegradation in karst soil-carbonate rock interface - Yunping Zhao; Hui Mu; Bill X. Hu; Chuanshun Zhi; Hui Wang; Linxian Huang; Fen Huang; Kai Han (Journal of Hazardous Materials, 2026)

Mechanistic insights into sulfidated nanoscale zero-valent iron enhanced methanogenesis: Electron redistribution and direct interspecies electron transfer-driven metabolic reconfiguration - Fangyuan Feng; Chunhui Zhao; Yinguang Chen; Yongfang Zhang; Xiaonong Hu; Hui Mu; Wen Zhang (Bioresource Technology, 2026)

Seismic Response of Utility Tunnels Under Oblique SV Wave Incidence in Horizontally Nonhomogeneous Sites - De-long Huang; Hui-yue Wang; Yang Ding; Hang Cen; Qiang Liu; Zhong-ling Zong; Dian-rui Mu; Ai-ping Tang (Geotechnical and Geological Engineering, 2026)

Impact of salinity on nitrogen cycling and microbial community functional potential in groundwater of the Yellow river delta - Huan Wang; Chuanshun Zhi; Yufei Jiao; Dan Xu; Wenfeng Gao; Yawei Kou; Xiancang Wu; Jing Bai; Hui Mu; Houliang Lu; Xiaonong Hu (Applied Geochemistry, 2026)

Physics-informed neural network for hydraulic prediction in open-channel water transfer projects with sparse monitoring data - Zhongbin Li; Tong Mu; Xin Li; Pengcheng Li; Jiangang Feng; Hui Xu; Chunsheng Liu; Shangtuo Qian (Water Research, 2025)

Anti-diabetic quinolone alkaloids from the fruits of Tetradium ruticarpum - Chun-Lin Zhao; Kai-Wen Kang; Zhi-Cheng Su; Hong-Yan Mu; Hui-Shan Guo; Hui-Zhen Chen; Ya-Ting Chen; Jing-Wei Jin; Ju-Cai Xu; Hong-Guang Li; Li-She Gan (Phytochemistry Letters, 2025)

Ore-forming process and fluid development at Nanpo Au deposit, Luang Prabang-Loei Belt (NW Laos): Evidence from H-O-S-Pb isotopes and inclusions - Wei Wang; Hui Li; Jie Gan; Fuhao Xiong; Yu Gan; Bin Wang; Junqing Mu; Huan Liu (Journal of Geochemical Exploration, 2025)

Development of a magnetite-oyster shell composite to improve methanogenesis in carbohydrate-rich wastewater treatment - Fangyuan Feng; Yichao Wang; Jingyang Luo; Chunhui Zhao; Yongfang Zhang; Chuanshun Zhi; Hui Mu (Journal of Environmental Chemical Engineering, 2025)

Golgi-associated TRAF6 as a regulator of protein convertase FURIN for insulin receptor precursor processing - Minjun Liu; Kun Zhou; Yang Sheng; Wen Zhang; Qiaoli Chen; Ziyue Chen; Xinyu Yang; Yuxin Jin; Fangtong Liu; Yinqiu Mu; Shu Su; Weikuan Feng; et al. (Science China Life Sciences, 2025)

Hydrochemical characteristics and circulation pattern of fault-type geothermal water in karst region: A case study in western Yunnan, China - Chuan Wen; Wenping Mu; Qiang Wu; Zhen Yang; Rong Li; Yubing Song; Hui Tan (Geothermics, 2025)

Reverse-tracing unravels microbial succession and flavor stratification driven by vertical physicochemical gradients in Zaopei fermentation - Boyang Xu; Shanshan Xu; Hao Zhou; Qinxiang Xu; Hui Zhang; Dongdong Mu; Xuefeng Wu; Eryong Zhao; Xingjiang Li (Food Chemistry, 2025)

Metagenomics and binning analysis unveiled the diversity and transfer patterns of antibiotic resistance genes in traditional pickled vegetables - Hui Wang; Xindi Mu; Tingting Su; Xiyuan Yang; Lei Xu; Di Yao; Liangyu Li (Food Bioscience, 2025)

Mapping urban ultrafine particle exposure in Guangzhou, China: Development of a high-resolution land-use regression framework for megacity - Qing-Guo Zeng; Qi-Zhen Wu; Bin Zhao; Mu-Wu Xu; Yun Zhu; Shi-Cheng Long; Guang-Hui Dong; Xiao-Wen Zeng (Environmental Research, 2025)

New pterosins from Hypolepis punctata - Liang Shen; Wenhao Mu; Peixin Wang; Maoni Ren; Yating Jia; Xiaoran Min; Jiajia He; Guozheng Huang; Hui Shen; Jianguo Cao (Journal of Natural Medicines, 2025)

Oyster shell immobilized nano zero-valent iron for enhancing methane production from carbohydrate-rich food waste: Characterization, performance, and mechanism - Xiaofan Ding; Wei Jiang; Fangyuan Feng; Bochang Feng; Yanfei Li; Yongfang Zhang; Chuanshun Zhi; Chunhui Zhao; Jingyang Luo; Hui Mu (Journal of Environmental Chemical Engineering, 2025)

NMR study on the distribution pattern of pore water in the process of freeze-thaw permeability enhancement of coal - Lei Qin; Pengfei Liu; Haifei Lin; Hui Wang; Ruizhe Wang; Miao Mu; Niandong Chen; Chengang Sun (Engineering Geology, 2025)

Development of a distributed monitoring method for soil suction based on optic-fiber sensing technique - Wen Mu; Chao-Sheng Tang; Qing Cheng; Jin-Jian Xu; Hui-Cong Hu; Qi-You Zhou (Engineering Geology, 2025)

Short-chain chlorinated paraffins at environmentally relevant doses disrupt glucose homeostasis and insulin signaling by macrophage-mediated inflammation - Ying-Wen Mu; Wen-Huan Yao; Hui Li; Cui-Li Zhang; Yan-Jing Zhang; Xiu-Ning Zhang; Ge Song; Xiu-Lan Zhao; Tao Zeng (Journal of Hazardous Materials, 2025)

Using ventilation hood during cooking reduced household air pollution exposure and brought cardiometabolic and pulmonary health benefits: A community-based, cluster-randomized controlled intervention study - Yueru Yang; Kuai Yu; Wending Li; Xuedan Xu; Chengyong Jia; Qi Yan; Xingxing Li; Hao Cai; Denghuan Hu; Hui Gao; Xuanwen Mu; Yuhui Lin; et al. (Journal of Hazardous Materials, 2025)

Soybean protein isolate hydrolysate addition during fermentation of soybean meal with Aspergillus oryzae enhances the release of umami components in subsequent hydrolysis process - Yihan Mu; Hui Kang; Xueying Song; Chenchen Cao; Dongxiao Sun-Waterhouse; Geoffrey I.N. Waterhouse; Mouming Zhao; Guowan Su (Food Bioscience, 2025)

Interlayer covalent bridging covalent organic polymers for highly efficient photocatalytic organic synthesis - Xia Zhao; Ai-Cen Li; Dan Yang; Yong-Hui Wang; Xin Mu; Cong Wang; Hua-Qiao Tan (Chemical Engineering Journal, 2025)

Accelerated C-F bond cleavage on sulfur vacancy-contained CoS2/MoS2 electrode featuring rich H* - Zhenglin Chen; Guangzhen Liu; Yuqi Hong; Lixia Yang; Xuefei Li; Hui Xiao; Yi Mu; Yue Li; Jianping Zou; Shenglian Luo (Journal of Hazardous Materials, 2025)

A new phenolic compound from Persicaria capitata - Lei He; Fei Zhong; Xing-Jun Chen; Ya-Ru Yang; Xue-Long Yan; Ming-Hui He; Xu Zhang; Mu-Zhen Wang; Yong-Qin Zeng; Qin-Feng Zhu; Zhu Zeng; Bo Tu; et al. (Natural Product Research, 2025)

Mechanism study of enhanced gas recovery and CO2 storage in naturally fractured carbonate reservoirs using a dual-permeability model coupled with association equation of state - Wei Xiong; Yu-Long Zhao; Lie-Hui Zhang; Shao-Mu Wen; Li-Li Liu; Zheng-Lin Cao; Cheng Cao; Xiang-Yu Liu; Xian-Yu Jiang (Gas Science and Engineering, 2025)

Characteristics of loess landslides under the effects of faults and rivers and their correlations with geological and surficial evolutionary processes - Qi-qi Liu; Wan-li Xie; Hui Yang; Ming Yan; Rong-sen Zhu; Ke Mu; Yi-lun Chang; Shengjie Di; Xiaoliang He; Xiaomin Liu; Ying Zhang (Bulletin of Engineering Geology and the Environment, 2025)

Insights into the interlinkages between rhizosphere soil extracellular enzymes and microbiome assemblages across soil profiles in grasslands - Xueqing Liu; Xifeng Fan; Mingcai Zhang; Hui Zhang; Yuesen Yue; Juying Wu; Wenjun Teng; Na Mu; Ke Teng; Haifeng Wen (Applied Soil Ecology, 2025)

Bacterial and archaeal community successions in high-salinity groundwater and their potential impact on arsenic cycling - Chuanshun Zhi; Xiaonong Hu; Zhuo Zhang; Baonan He; Jing Bai; Xiancang Wu; Hui Mu; Wenbo Chang; Fan Yang; Qi Qiu; Yuzheng Wang (Journal of Hydrology, 2025)

Microplastics and nanoplastics increase major adverse cardiac events in patients with myocardial infarction - Yun Zhang; Qianhui Gao; Qiang Gao; Mingcheng Xu; Ning Fang; Lin Mu; Xuejie Han; Hui Yu; Song Zhang; Yue Li; Yongtai Gong (Journal of Hazardous Materials, 2025)

Fluoride enrichment in geothermal waters based on H, O, Sr, and Li isotopes of the Taiyuan Basin, North China - Chang Lu; Ying Li; Xiaocheng Zhou; Yuwen Wang; Weiye Shao; Zhaojun Zeng; Zhaofei Liu; Dawei Liao; Hui Zhang; Huimin Mu (Journal of Asian Earth Sciences, 2025)

Photothermal-Triggered Radical Storm for Achieving Multi-Layered PD-L1 Inhibition in Cancer Theranostics - Houren Zhou; Yiyong Tang; Hui Liu; Mengyao Mu; Shangui Liu; Yuan Gao; Kai Guo; Mengmeng Zhang; Nengyi Ni; Feifei Teng; Hongzan Sun; Dawei Chen; et al. (Chemical Engineering Journal, 2025)

Targeting IGF1 to alleviate obesity through regulating energy expenditure and fat deposition - Ping Rong; Yinqiu Mu; Meiqin Wang; Liang Chen; Fangtong Liu; Yuxin Jin; Weikuan Feng; Kun Zhou; Hui Liang; Hong-Yu Wang; Shuai Chen (Science China Life Sciences, 2025)

Association Between Mixed Metal Exposures and Female Infertility: A Large Cross-sectional Study - Yunan He; Xiaoxiao Su; Zhiping Niu; Bolun Zhang; Hui Mu; Lu Wang; Yuanqing Yao; Xiaohong Wang (International Journal of Environmental Research, 2025)

Construction of the dynamic measurement algorithm for well inclination and azimuth in strapdown stable platform - Feng Sun; Rui Zhang; Yi-feng Wang; Wei Chen; Hui-dong Mu; Rui-wen Feng (Applied Geophysics, 2025)

Probiotic potential of lactic acid bacteria with antioxidant properties in modulating health: Mechanisms, applications, and future directions - Yuan Gao; Qimeng Liang; Junqi Sun; Xiaomeng Wu; Yinglong Song; Yunpeng Xu; Hui Nie; Jun Huang; Guangqing Mu (Food Bioscience, 2025)

Freeze–Thaw Response of Permeability and Absorption Channel Structure and Moisture Distribution in Different Coal Ranks - Lei Qin; Sinyin Lv; Shugang Li; Hui Wang; Pengfei Liu; Miao Mu; Jiawei Li (Natural Resources Research, 2025)

BPDE induces ferroptosis in hippocampal neurons through ACSL3 suppression - Hui He; Tingyu Ji; Yi Lyu; Fengjie Tian; Emily Mu; Sophia Mu; Jinping Zheng (NeuroToxicology, 2025)

A fusion of oncolytic viruses and bispecific T-cell engagers for triple negative breast cancer immunotherapy - Min Mu; Hui Li; Guoqing Wang; Bo Chen; Rangrang Fan; Nianyong Chen; Bingwen Zou; Aiping Tong; Gang Guo (Chemical Engineering Journal, 2025)

Lignin enhanced shape memory polyimide with superior mechanical property and performance - Qiang Wang; Xin Li; Mengxin Kan; Hui Gao; Shanshan Liu; Xingxiang Ji; Handong Mu; Zhuangzhuang Mao; Zhanhui Yuan (Chemical Engineering Journal, 2025)

Regulatory Roles and Therapeutic Potential of miR-122-5p in Hypoxic-Ischemic Brain Injury: Comprehensive Review - Abdulaziz S. Bamahel; Xun Sun; Wei Wu; Chenxi Mu; Jia Liu; Sheng Bi; Hui Xu (Cell Biochemistry and Biophysics, 2025)

Lithium isotope and mercury evidence for enhanced continental weathering and intense volcanism during the Ordovician-Silurian transition - Xiangrong Yang; Detian Yan; David J. Wilson; Philip A.E. Pogge von Strandmann; Xianyi Liu; Chunyao Liu; Hui Tian; Mu Liu; Liwei Zhang; Bao Zhang; Daizhao Chen (Geochimica et Cosmochimica Acta, 2025)

Ecological distribution of ammonia oxidizers in Yellow River sediments and their influencing factors - Xue Lou; Mengxin Xu; Mingyang Wang; Yining Jiang; Minggang Zheng; Hongyu Mu; Shuai Liu; Shaoping Kuang; Hui Chen; Zhiyao Wang (Environmental Research, 2025)

Dimeric PD-L1 specific affibody grafted Fe-based nanosheets for tumor-targeting dual-mode magnet resonance imaging and enhancement of Photothermal-Immunotherapy - Xinyu Zhang; Hui Liu; Chenyu Wang; Yuan Gao; Shiqi Zhao; Mengyao Mu; Ke Ren; Yufang Gong; Qing Fan; Xiao Sun (Chemical Engineering Journal, 2025)

Accessory minerals fingerprint post-collisional anatectic metamorphism in continental collision zones - Yong-Jie Yu; Ren-Xu Chen; Qiong-Xia Xia; Zhi-Hui Mu; Zhuang-Zhuang Yin; Guo-Chao Sun (Lithos, 2025)

Lignite degraded by Trichoderma citrinoviride: Products, processes and mechanisms - Xingyu Mu; Meitong Li; Jianhua Tian; Wenjiao Yuan; Hui Shen; Ruijie Zhang; Shuwei Li; Xin Feng; Xuening Fei; Yuhong Xie (International Biodeterioration & Biodegradation, 2025)

Extraction of betalaine from red pitaya peel using deep eutectic solvent and its research in films - Yanhong Liu; Xiwang Mu; Hui Wang; Mingyue Wang; Lingling Zhang; Guangrao Chen; Shuo Wang (Food and Bioproducts Processing, 2025)

Overcoming radiation-induced PD-L1 upregulation by novel gadolinium-palladium nanoplatforms for enhanced tumor radio-immunotherapy - Kai Guo; Hui Liu; Mengmeng Zhang; Nengyi Ni; Mengyao Mu; Ke Ren; Jiahui Chen; Qing Fan; Xueli Xu; Xiao Sun; Ximing Wang (Chemical Engineering Journal, 2025)

Improvement of NDVI mixture model for fractional vegetation cover estimation with consideration of shaded vegetation and soil components - Xihan Mu; Yang Yang; Hui Xu; Yuhan Guo; Yongkang Lai; Tim R. McVicar; Donghui Xie; Guangjian Yan (Remote Sensing of Environment, 2024)

Multi-omics analysis of metabolic differences in rape bee pollen fermented by single and mixed lactic acid bacterial strains - Zhiwei Sun; Lanhua Liu; Hui Zhang; Yousheng Wang; Jiayu Liu; Zhiwei Wang; Dongdong Mu; Xuefeng Wu; Xingjiang Li (Food Bioscience, 2024)

A multifunctional nanoplatform capable of dual action on tumor PD-L1 for enhanced cancer theranostics - Mengyao Mu; Mengmeng Zhang; Yufang Gong; Kai Guo; Hui Liu; Zeran Zhang; Tongxin Jiang; Houren Zhou; Qing Fan; Dianlong Jia; Yuqin Li; Xiao Sun (Chemical Engineering Journal, 2024)

Microbial transformation of lignite into methane: Insights from anaerobic-activated sludge systems - Ruijie Zhang; Meitong Li; Wenjiao Yuan; Xin Feng; Xuening Fei; Xingcheng Zhao; Gangzhen Jiao; Hui Shen; Xingyu Mu; Yuhong Xie (Bioresource Technology Reports, 2024)

Dynamic Mechanical Properties and Constitutive Model of Coal Rock Under Direct Tension - Hui Zhou; Huiqi Ren; Quanmin Xie; Hongen Zhang; Qiang Fu; Chaomin Mu (Rock Mechanics and Rock Engineering, 2024)

Lowering Schottky barrier in MoC-based cocatalyst via heteroatoms tunning for enhanced photocatalytic hydrogen evolution - Ru-zhou Miao; Yu-long Bao; Guang Yang; Ying-jie Sun; Xiao-jing Wang; Jun Zhao; Hui-ying Mu; Fa-tang Li (Chemical Engineering Journal, 2024)

Drying-rewetting alters arsenic ecotoxicity: From the perspective of enzyme-based functional diversity - Hui Huang; Haixia Tian; Ziquan Wang; Rongyu Mu; Chuanyou Wang; Mallavarapu Megharaj; Wenxiang He (Chemosphere, 2024)

Multi-objective optimization of clean utilization for zinc leaching residues by rotary kiln using neural network coupled modeling - Chen-Mu Zhang; Zhi Zan; Yao Shi; Hui-Quan Li; Lang-Ming Liu; Wei-Ping Liu; Wen-Jun Lin; Jing-Jing Shi; Ying-yan Hu; Xue Guan; Kuang-Yi Chen; Xiao Liu; et al. (Journal of Cleaner Production, 2024)

Neoproterozoic tungsten mineralization and associated granitic magmatism in the western Yangtze Block, South China: Mineralization age, petrogenesis and geodynamic implications - Zhongyuan Liu; Fuhao Xiong; Hui Li; Han Zhao; Tingting Gong; Jie Gan; Junqing Mu; Xiaohui Zeng (Precambrian Research, 2024)

Long-term exposure to major constituents of fine particulate matter and neurodegenerative diseases: A population-based survey in the Pearl River Delta Region, China - Qi-Zhen Wu; Hui-Xian Zeng; John Andersson; Anna Oudin; Katja M. Kanninen; Mu-Wu Xu; Shuang-Jian Qin; Qing-Guo Zeng; Bin Zhao; Mei Zheng; Nanxiang Jin; Wei-Chun Chou; et al. (Journal of Hazardous Materials, 2024)

Sediment provenance variations driven by sea level in the eastern Arabian Sea since the MIS 9 period: Evidence from geochemical proxies - Tongbing Fang; Shengfa Liu; Kaikai Wu; Hui Zhang; Peng Cao; Mu Huang; Lina Ai; Wenjing Qi; Jing Tao; Xuefa Shi (Journal of Asian Earth Sciences, 2024)

Superior performance of hybrid model in ungauged basins for real-time hourly water level forecasting – A case study on the Lancang-Mekong mainstream - Zhiqiang Dong; Hongchang Hu; Hui Liu; Baoligao Baiyin; Xiangpeng Mu; Jie Wen; Dengfeng Liu; Lajiao Chen; Guanghui Ming; Xue Chen; Xiaochen Li (Journal of Hydrology, 2024)

Isolation and identification of novel umami-enhancing peptides from fermented soybean meal hydrolysate by consecutive chromatography and UPLC–ESI–QTOF–MS/MS - Chenchen Cao; Hui Kang; Yihan Mu; Jianan Zhang; Weizheng Sun; Mouming Zhao; Guowan Su (Food Bioscience, 2024)

Linking carbon cycle perturbations to the Late Ordovician glaciation and mass extinction: A modeling approach - Junpeng Zhang; Chao Li; Yangyang Zhong; Xuejin Wu; Xiang Fang; Mu Liu; Daizhao Chen; Benjamin C. Gill; Thomas J. Algeo; Timothy W. Lyons; Yuandong Zhang; Hui Tian (Earth and Planetary Science Letters, 2024)

Jurassic integrative stratigraphy, biotas, and paleogeographical evolution of the Qinghai-Tibetan Plateau and its surrounding areas - Jianguo Li; Xin Rao; Lin Mu; Xiaohui Cui; Xin Li; Hui Luo; Peixue Liu (Science China Earth Sciences, 2024)

Glyphosate exposure affected longevity-related pathways and reduced survival in asian honey bees (Apis cerana) - Dong Zhi-Xiang; Li Wan-Li; LI Xi-Jie; Li Jia-Li; Zhang Jun; Zhao Chong-Hui; Huang Qi; Cao Zhe; Chen Yuan; Zhao Hong-Mu; Guo Jun; Tian Wen-Li (Chemosphere, 2024)

Research on improved YOLOx weed detection based on lightweight attention module - Huibin Zhu; Yuanyuan Zhang; Danlei Mu; Lizhen Bai; Xian Wu; Hao Zhuang; Hui Li (Crop Protection, 2024)

Provenance and sedimentary environment of REY-rich sediments from the Wharton Basin, Indian Ocean - Jia Li; Mu Huang; Miao Yu; Dongjie Bi; Xuefa Shi; Fengdeng Shi; Chengfei Hou; Zhaojun Song; Fangyu Shen; Aimei Zhu; Hui Zhang; Yonghua Wu; et al. (Journal of Asian Earth Sciences, 2024)

Genetic architecture of ecological divergence between Oryza rufipogon and Oryza nivara - Qing‐Lin Meng; Cheng‐Gen Qiang; Ji‐Long Li; Mu‐Fan Geng; Ning‐Ning Ren; Zhe Cai; Mei‐Xia Wang; Zi‐Hui Jiao; Fu‐Min Zhang; Xian‐Jun Song; Song Ge (Molecular Ecology, 2024)
Ecological divergence due to habitat difference plays a prominent role in the formation of new species, but the genetic architecture during ecological speciation and the mechanism underlying phenotypic divergence remain less understood. Two wild ancestors of rice ( Oryza rufipogon and Oryza nivara ) are a progenitor‐derivative species pair with ecological divergence and provide a unique system for studying ecological adaptation/speciation. Here, we constructed a high‐resolution linkage map and conducted a quantitative trait locus (QTL) analysis of 19 phenotypic traits using an F 2 population generated from a cross between the two Oryza species. We identified 113 QTLs associated with interspecific divergence of 16 quantitative traits, with effect sizes ranging from 1.61% to 34.1% in terms of the percentage of variation explained (PVE). The distribution of effect sizes of QTLs followed a negative exponential, suggesting that a few genes of large effect and many genes of small effect were responsible for the phenotypic divergence. We observed 18 clusters of QTLs (QTL hotspots) on 11 chromosomes, significantly more than that expected by chance, demonstrating the importance of coinheritance of loci/genes in ecological adaptation/speciation. Analysis of effect direction and v ‐test statistics revealed that interspecific differentiation of most traits was driven by divergent natural selection, supporting the argument that ecological adaptation/speciation would proceed rapidly under coordinated selection on multiple traits. Our findings provide new insights into the understanding of genetic architecture of ecological adaptation and speciation in plants and help effective manipulation of specific genes or gene cluster in rice breeding.

Melatonin inhibits atrazine-induced mitochondrial impairment in cerebellum of mice: Modulation of cGAS-STING-NLRP3 axis-dependent cell pyroptosis - Lin Liu; Mu-Zi Li; Ming-Hui Yao; Tian-Ning Yang; Yi-Xi Tang; Jin-Long Li (Science of The Total Environment, 2024)

Biogeography and diversity patterns of functional genes associated with C, N, P, S cycling processes across China classical sea sediments - Shuai Liu; Xin Huang; Hongyu Mu; Minggang Zheng; Shaoping Kuang; Hui Chen; Yan Xu; Dong Wang; Huan Liu; Xuan Li (Science of The Total Environment, 2024)

Ultrahigh moisture resistance, highly sensitive and flame retardancy wearable strain sensor for agile water rescue, fire alarm and human motion detection - Qinghua Liu; Jiehui Li; Jinmei He; Leihuan Mu; Yuyu Xue; Yue Zhao; Hui Liu; Cai-Li Sun; Mengnan Qu (Chemical Engineering Journal, 2024)

The Protective Effect of Chronic Intermittent Hypobaric Hypoxia on Preventing the Destruction of CD34+ Haematopoietic Stem Cells in Aplastic Anaemia by Modulating the Th1/Th2 Balance - Hui Guo; Yilin Zhao; Rui Mu; Guangdao Zhang; Shuxian Chen; Xinwei Cao; Kangcan Liu; Yiran Liu; Baiyun Dai; Yuan Zhou; Chuan Wang; Jing Yang (Stem Cell Reviews and Reports, 2024)

Abundance, characteristics and risk assessment of microplastics in aquatic sediments: A comparative study in the Yellow River and Yellow Sea - Shuai Liu; Hairong You; Hongyu Mu; Jiaxin Cheng; Shaoping Kuang; Fayuan Wang; Hui Chen; Minggang Zheng; Yan Xu; Tao Liu (Waste Management, 2023)

Significant enhancement of biomethane recovery in up-flow anaerobic sludge blanket reactor treating starch wastewater through oyster shells conditioning - Hui Mu; Qingyu Sun; Meng Zhong; Chunhui Zhao; Yongfang Zhang; Liguo Wang (Journal of Cleaner Production, 2023)

A sustainable strategy to transform cotton waste into renewable cellulose fiber self-reinforcing composite paper - Chan Wang; Jinhui Su; Taoyuan Liu; Shengbo Ge; Rock Keey Liew; Hui Zhang; Mu Naushad; Su Shiung Lam; Hui Suan Ng; Christian Sonne; Wei Fan (Journal of Cleaner Production, 2023)

Cerina litoralis gen. nov., sp. nov., a novel potential polysaccharide degrading bacterium of the family Flavobacteriaceae, isolated from marine sediment - Ya-Wei Wang; Xin-Hui Wang; Jing Zhang; Zong-Jun Du; Da-Shuai Mu (Antonie van Leeuwenhoek, 2023)

The carbon emission reduction effect of auditing outgoing officials' natural resource asset management——Evidence from China - Zhixiong Tan; Siying Mu; Hui Wang; Siying Chen; Jingwei Han (Science of The Total Environment, 2023)

Rapid identification of hazardous heavy metal-containing waste by combining EDXRF with machine learning: Taking zinc smelting waste as an example - Jing Teng; Yao Shi; Zuo-Hua Liu; Hui-Quan Li; Ming-Xing He; Zhi-Hong Li; Chen-Mu Zhang (Resources, Conservation and Recycling, 2023)

Effects of different types of granular activated carbon on methanogenesis of carbohydrate-rich food waste: Performance, microbial communities and optimization - Hui Mu; Xiaofan Ding; Xiaoyu Zhu; Liguo Wang; Yongfang Zhang; Chunhui Zhao (Science of The Total Environment, 2023)

Degradation of levofloxacin from antibiotic wastewater by pulse electrochemical oxidation with BDD electrode - Tao Xu; Xiting Tang; Meiting Qiu; Xiaoliu Lv; Yang Shi; Yihui Zhou; Yanfei Xie; Mu. Naushad; Su Shiung Lam; Hui Suan Ng; Christian Sonne; Shengbo Ge (Journal of Environmental Management, 2023)

Characterization of the differences in aroma-active compounds in strong-flavor Baijiu induced by bioaugmented Daqu using metabolomics and sensomics approaches - Yu Mu; Jun Huang; Rongqing Zhou; Suyi Zhang; Hui Qin; Hanlan Tang; Qianglin Pan; Huifang Tang (Food Chemistry, 2023)

Maternal exposure to neonicotinoid insecticides and fetal growth restriction: A nested case-control study in the guangxi Zhuang birth cohort - Dongxiang Pan; Mengrui Lin; Changhui Mu; Chuanxiang Yu; Bowen Ye; Jun Liang; Yonghong Sheng; Dongping Huang; Shun Liu; Xiaoyun Zeng; Hui Juan Jennifer Tan; Virasakdi Chongsuvivatwong; et al. (Chemosphere, 2023)

C21 steroids from the roots of Marsdenia tenacissima - Jin-Ling Liu; Hong-Tao Xu; Dan-Dan Mu; Xiao Han; Ting-Ting Du; Yong-li Wang; Xiao-Hui Wei; Gui-Xin Chou (Phytochemistry, 2023)

Multi-omics reveals 2-bromo-4,6-dinitroaniline (BDNA)-induced hepatotoxicity and the role of the gut-liver axis in rats - Fuchang Deng; Guangqiu Qin; Yuanyuan Chen; Xu Zhang; Mu Zhu; Min Hou; Qiao Yao; Wen Gu; Chao Wang; Hui Yang; Xudong Jia; Chongming Wu; et al. (Journal of Hazardous Materials, 2023)

Small-molecular cyclic peptide exerts viability suppression effects on HepG2 cells via triggering p53 apoptotic pathways - Hui Zhang; Huanli Zhang; Jingchun Wang; Li Fan; Weijie Mu; Yingxue Jin; Zhiqiang Wang (Chemico-Biological Interactions, 2023)

Lactate Improves Long-term Cognitive Impairment Induced By Repeated Neonatal Sevoflurane Exposures Through SIRT1-mediated Regulation of Adult Hippocampal Neurogenesis and Synaptic Plasticity in Male Mice - Li-Li Qiu; Xiao-Xiang Tan; Jiao-Jiao Yang; Mu-Huo Ji; Hui Zhang; Chunjie Zhao; Jiang-Yan Xia; Jie Sun (Molecular Neurobiology, 2023)

Study on a galactose decomposition strain of Lactiplantibacillus plantarum MWLp-4 from human milk: Safety evaluating and key genes analysis of potential probiotic function - Xiaomei Zhang; Junhao Jin; Jinghong Zhao; Hui Nie; Guangqing Mu; Xiaomeng Wu (Food Bioscience, 2023)

Impacts of cold-extrusion whey protein isolate synergized with inulin on physicochemical characteristics of fermented milk - Hongyu Li; Jialu Sun; xin Mu; Munkh-Amgalan Gantumur; Xianqi Liu; Jinpeng Li; Sinan Mu; Minghan Zhang; Zhanmei Jiang; Hui Tian (Food Bioscience, 2023)

H2S-releasing versatile hydrogel dressing with potent antimicrobial, anti-inflammatory, epithelialization and angiogenic capabilities for diabetic wound healing - Jiale Chen; Zhixiang Mu; Dongfan Chen; Chen Huang; Ting Jin; Lin Li; Youyun Zeng; Qiang Zhou; Yanmei Zhang; Hongli Mao; Hui Deng; Xinkun Shen; et al. (Chemical Engineering Journal, 2023)

Determination of potential sources of heavy metals in patients with urothelial carcinoma in central Taiwan: a biomonitoring case–control study - Chi-Jung Chung; Hui-Ling Lee; Chao-Hsiang Chang; Chih-Da Wu; Chiu-Shong Liu; Mu-Chi Chung; Hui-Tsung Hsu (Environmental Geochemistry and Health, 2023)

Short-term effects of individual exposure to PM2.5 on hospital admissions for myocardial infarction and stroke: a population-based case-crossover study in Guangzhou, China - Jie-Qi Jin; Guo-Zhen Lin; Shuang-Ying Wu; Mu-Rui Zheng; Hui Liu; Xiang-Yi Liu; Min-Qian Yan; Zhao-Yue Chen; Chun-Quan Ou (Environmental Science and Pollution Research, 2023)

Remediation and recovery of Kariba weed as emerging contaminant in freshwater and shellfish aquaculture system via solvothermal liquefaction - Elfina Azwar; Wan Adibah Wan Mahari; Rock Keey Liew; Muhammad Zulhilmi Ramlee; Meenakshi Verma; William Woei Fong Chong; Wanxi Peng; Hui Suan Ng; Mu. Naushad; Christian Sonne; Su Shiung Lam (Science of The Total Environment, 2023)

Derivation of copper water quality criteria in Bohai Bay for the protection of local aquatic life and the ecological risk assessment - Yang Li; Di Mu; Hong-Qing Wu; Hai-Jiao Liu; Yong-Hui Wang; Guo-Chen Ma; Xue-Min Duan; Jian-Jun Zhou; Chun-Ming Zhang; Xing-Hua Lu; Xian-Hua Liu; Jun Sun; et al. (Marine Pollution Bulletin, 2023)

Flavonoids derived from licorice suppress LPS-induced acute lung injury in mice by inhibiting the cGAS-STING signaling pathway - Jincai Wen; Shuanglin Qin; Yurong Li; Ping Zhang; Xiaoyan Zhan; Mingxia Fang; Ce Shi; Wenqing Mu; Wen Kan; Jia Zhao; Siwen Hui; Manting Hou; et al. (Food and Chemical Toxicology, 2023)

Production, identification and characterization of antioxidant peptides from potato protein by energy-divergent and gathered ultrasound assisted enzymatic hydrolysis - Hui Liu; Hong-Nan Sun; Miao Zhang; Tai-Hua Mu; Nasir Mehmood Khan (Food Chemistry, 2023)

Comprehensive analysis for the bioturbation effect of space mutation and biofortification on strong-flavor Daqu by high-throughput sequencing, volatile analysis and metabolomics - Yu Mu; Jun Huang; Rongqing Zhou; Suyi Zhang; Hui Qin; Yi Dong; Chao Wang; Xiaojun Wang; Qianglin Pan; Huifang Tang (Food Chemistry, 2023)

Atmospheric ammonia in the rural North China Plain during wintertime: Variations, sources, and implications for HONO heterogeneous formation - Pengfei Liu; Hui Chen; Yifei Song; Chaoyang Xue; Can Ye; Xiaoxi Zhao; Chenglong Zhang; Junfeng Liu; Yujing Mu (Science of The Total Environment, 2023)

Effect of 4 °C and ice temperature on umami-enhancing nucleotides of conditioned pork - Yin Zhang; Yingjie Zhang; Hui Li; Ting Bai; Qin Qian; Haichuan Peng; Yunlong Mu; Linguo Wang; Baohua Liu; Jie Chen; Zhongli Pan; Dayu Liu; et al. (Food Chemistry, 2023)

Structures of the xyloglucans in the monocotyledon family Araceae (aroids) - Shih-Yi Hsiung; Jing Li; Balazs Imre; Mu-Rong Kao; Hsien-Chun Liao; Damao Wang; Chih-Hui Chen; Pi-Hui Liang; Philip J. Harris; Yves S. Y. Hsieh (Planta, 2023)
Main conclusion The xyloglucans of all aquatic Araceae species examined had unusual structures compared with those of other non-commelinid monocotyledon families previously examined. Abstract The aquatic Araceae species Lemna minor was earlier shown to have xyloglucans with a different structure from the fucogalactoxyloglucans of other non-commelinid monocotyledons. We investigated 26 Araceae species (including L. minor ), from five of the seven subfamilies. All seven aquatic species examined had xyloglucans that were unusual in having one or two of three features: < 77% XXXG core motif [ L. minor (Lemnoideae) and Orontium aquaticum (Orontioideae)]; no fucosylation [ L. minor (Lemnoideae), Cryptocoryne aponogetonifolia , and Lagenandra ovata (Aroideae, Rheophytes clade)]; and > 14% oligosaccharide units with S or D side chains [ Spirodela polyrhiza and Landoltia punctata (Lemnoideae) and Pistia stratiotes (Aroideae, Dracunculus clade)]. Orontioideae and Lemnoideae are the two most basal subfamilies, with all species being aquatic, and Aroideae is the most derived. Two terrestrial species [ Dieffenbachia seguine and Spathicarpa hastifolia (Aroideae, Zantedeschia clade)] also had xyloglucans without fucose indicating this feature was not unique to aquatic species.

The use of microbes in culture of harpacticoid copepod (Tigriopus japonicus Mori) for suppression of Vibrio and enhancement of population growth, enzyme activity and microbial longevity - Javad Sahandi; Patrick Sorgeloos; Hui Xiao; Fanghong Mu; Xianghong Wang; Zizhong Qi; Yanfen Zheng; Xuexi Tang (Aquaculture, 2023)

Environmental impact of typical zinc smelting that implements solid waste collaborative utilization in China - Wei-Ning Liu; Yao Shi; Chen-Mu Zhang; Lang-Ming Liu; Hui-Quan Li; Bin Lu; Yuan-Bo Xie; Cai-Bei Zhuang; Tian-You Sun; Wei-Ping Liu; Xue Guan; Ying-Yan Hu (The International Journal of Life Cycle Assessment, 2022)

An association study on the risk, glucocorticoids effectiveness, and prognosis of systemic lupus erythematosus: insight from mitochondrial DNA copy number - Zhen Li; Qi-Qun Zong; Chun-Xia Zhai; Guang-Hui Yu; Wan-Qin Hu; Yu-Hua Wang; Lin-Lin Wang; Zi-Ye Yan; Ting-Yu Zhang; Ying Teng; Shuang Liu; Jing Cai; et al. (Immunologic Research, 2022)

Geochemical evolution of structure-bedding controlled hydrothermal dolomites of the Kinta Valley, Western Malaysia - P. Xin Hui; R. Nagarajan; Mu. Ramkumar; T. F. Ng; Nur I. Taib; M. J. Mathew; B. Sautter; N. A. Siddiqui; M. C. Poppelreiter (Carbonates and Evaporites, 2022)
Study of secondary dolomitization and documentation of the evolution of basinal fluids and host rock, especially that of fine-grained deepwater carbonate mudstone are of interest toward of reservoir characterization. From this perspective, field characteristics in relation to mineralogy, petrography and geochemistry of the Paleaozoic carbonates of the Kinta Valley, Peninsular Malaysia, were investigated and documented. A total of 33 samples were collected across the various degree of dolomitization and analyzed for their petrographic properties ( n = 55), while mineralogical and geochemical compositions ( n = 33) were analyzed using XRD, ICP and ICPMS analysis, respectively. These analyses were performed to elucidate the diagenetic events, episodic dolomitization and development of fluid evolution as a function of regional tectono-thermal events during the Permian to Cenozoic. It is interpreted that the host calcareous mudstones (HCMs) were deposited in oxygenated, open marine seawaters. The studied samples retain the original seawater characteristics despite negligible, minor alterations of REE characteristics due to diagenesis and detrital input. Though the concentrations and trends of REEs of the dolomitic facies are modified to a certain extent, their affinities with HCMs are preserved. Enrichments of Mg, Mn, Na and depletion of Sr are linked to the effect of dolomitization under the open system of diagenesis. The redox conditions fluctuated to show distinct, recognizable variations between different dolomite phases. The MREE enrichments with other trace elements such as Mn, Fe and low Sr content indicate the association of diagenetic fluids with deep-circulating crustal hydrothermal fluids. Hydrothermal influence has been recorded along the fractures, which might have originated from the sub-surface litho units and facilitated episodic dolomitization, especially during significant tectono-thermal events. This study affirms that the occurrence, geochemical and mineralogical evolution of the dolomites of the Kinta Valley were controlled by magmatic events, whereas the intensity of replacement dolomitization was controlled by host rock texture, varied bulk chemistry of host rock, circulating fluid and temperature.

Pollution heaven or pollution halo? Assessing the role of heterogeneous environmental regulation in the impact of foreign direct investment on green economic efficiency - Hui Zheng; Li Zhang; Weiling Song; Hairong Mu (Environmental Science and Pollution Research, 2022)

Efficient degradation of semi-coking wastewater in three-dimensional electro-Fenton by CuFe2O4 heterocatalyst - Wen-wen Gao; Ting Su; Wei Zhao; Zhi-fang Zhang; Miao Mu; Yong-hui Song; Xue-xue Zhang; Xin-yu Liu (Environmental Science and Pollution Research, 2022)

Protective Effects of Sepia Ink Melanin on Hepatic Tissue in Streptozotocin-Induced Diabetic Mice - Xiaopeng Wang; Meng Han; Hui Dong; Yun Zhao; Weiwei Song; Chunlin Wang; Changkao Mu; Ronghua Li (Journal of Ocean University of China, 2022)

Late Mesozoic rifting and its deep dynamic mechanisms in the central Sulu orogenic belt: Records from Lingshan Island - Tengfei Zhou; Yaoqi Zhou; Nina Søager; Paul Martin Holm; Zhenkai Zhang; Jun Wang; Zhao Liang; Hongyu Mu; Yanjun Cheng; Feifei Liu; Miao Wang; Yue Zhang; et al. (Science China Earth Sciences, 2022)

Xinfangfangia pollutisoli sp. nov., Isolated from Clopyralid-Contaminated Soil - Yang Mu; Jia-Yi Peng; Hui-Ping Wang; Yue Song; Hong-Mei Wang; Qing Chen; Kai Chen (Current Microbiology, 2022)

Quantifying soil nitrous oxide emissions in spring freezing-thawing period over different vegetation types in Northeast China - Bin Wu; Chang-cheng Mu; Hui Liu; Ya-kun Xu; Yue Zhang; Jia-shuo Yang; Wen-nian Xu (Journal of Mountain Science, 2022)

Relationships of multiple metals exposure, global DNA methylation, and urothelial carcinoma in central Taiwan - Hui-Tsung Hsu; Hui-Ling Lee; Hsu-Hui Cheng; Chao-Hsiang Chang; Chiu-Shong Liu; Po-Jen Hsiao; Han Chang; Chi-Shun Lien; Mu-Chi Chung; Chi-Jung Chung (Archives of Toxicology, 2022)

Functional characterization of tyrosine decarboxylase genes that contribute to acteoside biosynthesis in Rehmannia glutinosa - Yan Hui Yang; Mu Rong Yang; Jian Yu Zhu; Ke Wei Dong; Yan Jie Yi; Rui Fang Li; Lei Zeng; Chang Fu Zhang (Planta, 2022)

Comparative phylogeography of Acanthocalyx (Caprifoliaceae) reveals distinct genetic structures in the Himalaya–Hengduan Mountains - Qi-Yong Mu; Chih-Chieh Yu; Yan Wang; Ting-Shen Han; Hui Wang; Wen-Na Ding; Qiu-Yue Zhang; Shook Ling Low; Quan-Jing Zheng; Chuan Peng; Zheng-Yan Hu; Yao-Wu Xing (Alpine Botany, 2022)

A contribution to knowledge of Gyroporus (Gyroporaceae, Boletales) in China: three new taxa, two previous species, and one ambiguous taxon - Hui-Jing Xie; Li-Ping Tang; Man Mu; Yu-Guang Fan; Shuai Jiang; Ming-Sheng Su; Zhi-Qun Liang; Nian-Kai Zeng (Mycological Progress, 2022)

A landslide in Heifangtai, northwest of the Chinese Loess Plateau: triggered factors, movement characteristics, and failure mechanism - Jia-xu Kong; Jian-qi Zhuang; Jie-wei Zhan; Zheng-wei Bai; Yan-qiu Leng; Peng-hui Ma; Jian-bing Peng; Zuo-peng Wang; Tian-feng Gu; Jia-xing Sun; Fan-chen Zhang; Yuan-jun Xu; et al. (Landslides, 2021)

Lipocalin-2-induced proliferative endoplasmic reticulum stress participates in Kawasaki disease-related pulmonary arterial abnormalities - Zhaoling Shi; Yue Yin; Chen Li; Hui Ding; Nan Mu; Yishi Wang; Shanshan Jin; Heng Ma; Manling Liu; Jie Zhou (Science China Life Sciences, 2021)

Genome analysis of Salmonella phage vB_SalM_8-19 (genus Rosemountvirus) - Cong Cong; Wei Bing Dong; Cui Hui Jing; Yuan Yu Yu; Xu Yong Ping; Wang Li Li; Li Shu Ying; Li Ji Bin; Xu Mu; Li Xiao Yu (Archives of Microbiology, 2021)

Polymorphisms in the DC-SIGN gene and their association with the severity of hand, foot, and mouth disease caused by enterovirus 71 - Ya-Ping Li; Mu-Qi Wang; Chen-Rui Liu; Hui-Ling Deng; Yuan Wu; Shuang-Suo Dang; Li-Hong Xu (Archives of Virology, 2021)

Interest-activity symptom severity predicts response to ketamine infusion in treatment-resistant depression - Mu-Hong Chen; Wei-Chen Lin; Hui-Ju Wu; Ya-Mei Bai; Cheng-Ta Li; Shih-Jen Tsai; Chen-Jee Hong; Pei-Chi Tu; Tung-Ping Su (Psychopharmacology, 2021)

A plant virus mediates interspecific competition between its insect vectors in Capsicuum annuum - Yong Chen; Xue Zheng; Hui Wei; Yong-Dui Chen; Kuan-Yu Zheng; Ye Mu; Xing-Yue Zhao; Li-Hua Zhao; Yu-Lin Gao; Li-Min Zheng; Jie Zhang (Journal of Pest Science, 2021)

Relationships among cigarette smoking, urinary biomarkers, and urothelial carcinoma risk: a case-control study - Chi-Jung Chung; Hui-Tsung Hsu; Chao-Hsiang Chang; Sheng-Wei Li; Chiu-Shong Liu; Mu-Chi Chung; Guo-Wei Wu; Wei-Ting Jung; Yen-Jung Kuo; Hui-Ling Lee (Environmental Science and Pollution Research, 2020)

The anti-inflammatory drug dimethyl itaconate protects against colitis-associated colorectal cancer - Qian Wang; Xin Ling Li; Yan Mei; Jia-Chong Ye; Wei Fan; Guang-Hui Cheng; Mu-Sheng Zeng; Guo-Kai Feng (Journal of Molecular Medicine, 2020)

Vitamin D receptor gene methylation in patients with hand, foot, and mouth disease caused by enterovirus 71 - Ya-Ping Li; Hui-Ling Deng; Wen-Jun Wang; Mu-Qi Wang; Mei Li; Yu-Feng Zhang; Jun Wang; Shuang-Suo Dang (Archives of Virology, 2020)

A bacterial polysaccharide biosynthesis-related gene inversely regulates larval settlement and metamorphosis of Mytilus coruscus - Li-Hua Peng; Xiao Liang; Rui-Heng Chang; Jia-Yi Mu; Hui-E Chen; Asami Yoshida; Kiyoshi Osatomi; Jin-Long Yang (Biofouling, 2020)

Anti-hypertensive effects of Radix Rehmanniae and its active ingredients - Chiu-Haw Chao; Jue-Liang Hsu; Mu-Fen Chen; Ya-Hu Shih; Chia-Hui Lee; Mei-Li Wu; Chi-I Chang (Natural Product Research, 2020)

Differential diagnosis of the cranial perforations on the Early Iron Age along the Ancient Silk Road in Xinjiang, China - Xiaoya Zhan; Ai-Jia Mu; Liang Chen; Qun Zhang; Yong Wu; Wanglin Hu; Hui-Yuan Yeh (Archaeological and Anthropological Sciences, 2019)
Bioarcheologists and pathologists favor trauma on the skeletons since it could reflect the human activities and interpersonal relationship in the past. In this paper, we present the pattern of two cranial perforations found on an adult male buried in the Xiaoshankou Cemetery, which was part of the Silk Road region, dating back to the early Iron Age. The specimen of interest presents two perforations on his skull, with one perforation located on the anterior part of the left parietal bone, while the other is on the occipital bone near to the lambda. The morphology of the perforations indicates perimortem traumatic lesions, probably produced by a sharp force weapon, possibly arrowhead, through one shot. The interpretation of the penetrating lesions on this cranium offers new perspectives when diagnosing perforations on the skulls in the Xinjiang region. Meanwhile, this study adds literature to the patterns of violence in Xinjiang region as well.

Measurement of urinary arsenic profiles and DNA hypomethylation in a case–control study of urothelial carcinoma - Chi-Jung Chung; Hui-Ling Lee; Chao-Hsiang Chang; Han Chang; Chiu-Shong Liu; Wei-Ting Jung; Huei-Ju Liu; Saou-Hsing Liou; Mu-Chi Chung; Yu-Mei Hsueh (Archives of Toxicology, 2019)

Resina draconis inhibits the endoplasmic-reticulum-induced apoptosis of myocardial cells via regulating miR-423-3p/ERK signaling pathway in a tree shrew myocardial ischemia–reperfusion model - Tian-Rui Yang; Tong Zhang; Ning-Hui Mu; Li-Bo Ruan; Jin-Lan Duan; Rong-Ping Zhang; Yun-Bo Miao (Journal of Biosciences, 2019)

Four new phenolic constituents from the rhizomes of Gastrodia elata Blume - Zhi-Wei Wang; Yun Li; Da-Hui Liu; Yan Mu; Hong-Jing Dong; Hong-Lei Zhou; Lan-Ping Guo; Xiao Wang (Natural Product Research, 2019)

Tilapia fisheries in Guangdong Province, China: Socio‐economic benefits, and threats on native ecosystems and economics - Dang En Gu; Fan Dong Yu; Ye Xin Yang; Meng Xu; Hui Wei; Du Luo; Xi Dong Mu; Yin Chang Hu (Fisheries Management and Ecology, 2019)
Tilapia is one of the groups of fish species most widely cultured globally. China has been the largest producer of tilapia in the world since 1990s. Guangdong Province produces almost 40% of all tilapia in China because of its suitable geography and weather conditions, and tilapia culture has brought considerable economic benefits. Unfortunately, many of the biological traits that make tilapia popular for culture also contribute to its success as an invader. Tilapia has invaded natural waters and has become the dominant fish in many rivers of Guangdong Province, causing economic loss in capture fisheries, and affecting native fish species, biodiversity and aquatic ecosystems. Poor fishery management, water quality degradation and biodiversity loss have all facilitated the tilapia invasion. Tilapia have filled the niches left vacant by now locally extinct native species resulting from environmental changes in freshwater ecosystems of the province. The introduction of tilapia has both advantages and disadvantages, which should be managed to use effectively the various tilapia species in aquaculture while controlling their spread in natural waters.

Atorvastatin ameliorates the contractile dysfunction of the aorta induced by organ culture - Feng Zhou; Fang Rao; You-Qing Deng; Hui Yang; Su-Juan Kuang; Fei-Long Wu; Shu-Lin Wu; Yu-Mei Xue; Xiao-Mu Wu; Chun-Yu Deng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Hoeflea prorocentri sp. nov., isolated from a culture of the marine dinoflagellate Prorocentrum mexicanum PM01 - Qiao Yang; Zhi-Wei Jiang; Cheng-Hui Huang; Ruo-Nan Zhang; Ling-Zhi Li; Guang Yang; Li-Juan Feng; Guang-Feng Yang; Heng Zhang; Xiao-Ling Zhang; Jun Mu (Antonie van Leeuwenhoek, 2018)

Functional Role of Matrix gla Protein in Glioma Cell Migration - Mu-Hui Fu; Chih-Yen Wang; Yun-Ti Hsieh; Kuan-Min Fang; Shun-Fen Tzeng (Molecular Neurobiology, 2018)

Cadmium and lead accumulations and agronomic quality of a newly bred pollution-safe cultivar (PSC) of water spinach - Ying-Ying Huang; Yang-Xiu Mu; Chun-Tao He; Hui-Ling Fu; Xue-Song Wang; Fei-Yue Gong; Zhong-Yi Yang (Environmental Science and Pollution Research, 2018)

Underestimated effects of sediments on enhanced startup performance of biofilm systems for polluted source water pretreatment - Zheng-hui Lv; Jing Wang; Guang-feng Yang; Li-juan Feng; Jun Mu; Liang Zhu; Xiang-yang Xu (Biodegradation, 2018)

A method for alpine wetland delineation and features of border: Zoigê Plateau, China - Yaomin Zheng; Zhenguo Niu; Peng Gong; Mengna Li; Lile Hu; Lei Wang; Yuxiang Yang; Haijun Gu; Jinrong Mu; Gejia Dou; Hui Xue; Lin Wang; et al. (Chinese Geographical Science, 2017)

Response of performance and bacterial community to oligotrophic stress in biofilm systems for raw water pretreatment - Li-juan Feng; Rong Jia; Jing-ya Sun; Jing Wang; Zheng-hui Lv; Jun Mu; Guang-feng Yang (Biodegradation, 2017)

Repeated Neonatal Sevoflurane Exposure-Induced Developmental Delays of Parvalbumin Interneurons and Cognitive Impairments Are Reversed by Environmental Enrichment - Mu-huo Ji; Zhong-yun Wang; Xiao-ru Sun; Hui Tang; Hui Zhang; Min Jia; Li-li Qiu; Guang-fen Zhang; Yong G. Peng; Jian-jun Yang (Molecular Neurobiology, 2017)

Puerarin-7-O-glucuronide, a water-soluble puerarin metabolite, prevents angiotensin II-induced cardiomyocyte hypertrophy by reducing oxidative stress - Ning Hou; Bin Cai; Cai-Wen Ou; Zhen-Hui Zhang; Xia-Wen Liu; Mu Yuan; Gan-Jian Zhao; Shi-Ming Liu; Long-Gen Xiong; Jian-Dong Luo; Cheng-Feng Luo; Min-Sheng Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

Expression of SoxC Transcription Factors during Zebrafish Retinal and Optic Nerve Regeneration - Zhaoxia Mu; Shuqiang Zhang; Chunjiao He; Haitao Hou; Dong Liu; Nan Hu; Hui Xu (Neuroscience Bulletin, 2017)

NOX2 Mediated-Parvalbumin Interneuron Loss Might Contribute to Anxiety-Like and Enhanced Fear Learning Behavior in a Rat Model of Post-Traumatic Stress Disorder - Fang-fang Liu; Lin-dong Yang; Xiao-ru Sun; Hui Zhang; Wei Pan; Xing-ming Wang; Jian-jun Yang; Mu-huo Ji; Hong-mei Yuan (Molecular Neurobiology, 2016)

Reactive Oxygen Species-mediated Loss of Phenotype of Parvalbumin Interneurons Contributes to Long-term Cognitive Impairments After Repeated Neonatal Ketamine Exposures - Hui Zhang; Xiao-ru Sun; Jing Wang; Zhen-zhen Zhang; Hong-ting Zhao; Hui-hui Li; Mu-huo Ji; Kuan-yu Li; Jian-jun Yang (Neurotoxicity Research, 2016)

Seed predators can increase nectar volumes in an alpine daisy: but do the insects benefit? - Junpeng Mu; Yan Chen; Yulian Yang; Ronghua Fu; Hui Wang; Stephen G. Compton (Plant Ecology, 2016)

Methylenebisnicotiflorin: a rare methylene-bridged bisflavonoid glycoside from ripe Pu-er tea - Mu-Ke Tao; Min Xu; Han Zhang; Hui Chen; Chang Liu; Hong-Tao Zhu; Dong Wang; Chong-Ren Yang; Ying-Jun Zhang (Natural Product Research, 2016)

Hypermethylation of Hippocampal Synaptic Plasticity-Related genes is Involved in Neonatal Sevoflurane Exposure-Induced Cognitive Impairments in Rats - Ling-sha Ju; Min Jia; Jie Sun; Xiao-ru Sun; Hui Zhang; Mu-huo Ji; Jian-jun Yang; Zhong-yun Wang (Neurotoxicity Research, 2016)

Vertical motions of tide gauge stations near the Bohai Sea and Yellow Sea - ShouHua Liu; ChangLin Chen; KeXiu Liu; Lin Mu; Hui Wang; XinRong Wu; JianLi Zhang; XiaoFeng Duan; Jia Gao (Science China Earth Sciences, 2015)

Glucocorticoid Receptor β Acts as a Co-activator of T-Cell Factor 4 and Enhances Glioma Cell Proliferation - Qian Wang; Pei-Hua Lu; Zhi-Feng Shi; Yan-Juan Xu; Jie Xiang; Yan-Xia Wang; Ling-Xiao Deng; Ping Xie; Ying Yin; Bin Zhang; Hui-Jun Mu; Wei-Zhen Qiao; et al. (Molecular Neurobiology, 2015)

Distributive directions of gully system in Yuanmou Dry-hot Valley - Hongli Mu; Qingchun Deng; Bin Zhang; Fachao Qin; Mingliang Luo; Hui Liu; Shoujiang Liu (Arabian Journal of Geosciences, 2015)

Environmental Enrichment Ameliorates Neonatal Sevoflurane Exposure-Induced Cognitive and Synaptic Plasticity Impairments - Mu-huo Ji; Xing-ming Wang; Xiao-ru Sun; Hui Zhang; Ling-sha Ju; Li-li Qiu; Jiao-jiao Yang; Min Jia; Jing Wu; Jianjun Yang (Journal of Molecular Neuroscience, 2015)

A sensitive and accurate quantification method for the detection of hepatitis B virus covalently closed circular DNA by the application of a droplet digital polymerase chain reaction amplification system - Di Mu; Liang Yan; Hui Tang; Yong Liao (Biotechnology Letters, 2015)

Vimentin Regulates Neuroplasticity in Transected Spinal Cord Rats Associated with micRNA138 - Bao-Jiang Qian; Ling You; Fei-Fei Shang; Jia Liu; Ping Dai; Na Lin; Mu He; Ran Liu; Yuan Zhang; Yang Xu; Yun-Hui Zhang; Ting-Hua Wang (Molecular Neurobiology, 2015)

Comparison of Bradysia odoriphaga Yang and Zhang reared on artificial diet and different host plants based on an age-stage, two-sex life table - Peng Zhang; Feng Liu; Wei Mu; Qiuhong Wang; Hui Li (Phytoparasitica, 2015)

Degradation characteristics of permafrost under the effect of climate warming and engineering disturbance along the Qinghai–Tibet Highway - Hui Peng; Wei Ma; Yan-hu Mu; Long Jin; Kun Yuan (Natural Hazards, 2015)

Toxic effects of HgCl2 on activities of SOD, AchE and relative expression of SOD, AChE, CYP1A1 of zebrafish - He Zhen; Mu Wen; Yang Yang; Zhang Can; Geng Hui; Xiong Li; Liu Deli (Ecotoxicology, 2014)

Similarities between optimal precursors for ENSO events and optimally growing initial errors in El Niño predictions - Mu Mu; Yanshan Yu; Hui Xu; Tingting Gong (Theoretical and Applied Climatology, 2014)

An Informetric Profile of Water Resources Management Literatures - Jun-Lin Ren; Peng-Hui Lyu; Xin-Mu Wu; Fei-Cheng Ma; Zhi-Zhang Wang; Gang Yang (Water Resources Management, 2013)

Effects of 1,1,1-trichloroethane on enzymatic activity and bacterial community in anaerobic microcosm form sequencing batch reactors - Hui Li; Wei Zhang; Lu Li; Yong-Di Liu; Kuang-Fei Lin; Shu-Guang Lu; Bo-Zhong Mu; Xiao-Ming Du; Qiang Lu; Qian Zhang; Ting-Ting Shen; Bing-Zhi Li; et al. (Ecotoxicology, 2012)

Clinical significance of peritumoral lymphatic vessel density and lymphatic vessel invasion detected by D2-40 immunostaining in FIGO Ib1-IIa squamous cell cervical cancer - Ying Xiong; Li-Ping Cao; Hui-Lan Rao; Mu-Yan Cai; Li-Zhi Liang; Ji-Hong Liu (Cell and Tissue Research, 2012)

Participatory agroforestry development for restoring degraded sloping land in DPR Korea - Jianchu Xu; Meine van Noordwijk; Jun He; Kwang-Ju Kim; Ryong-Song Jo; Kon-Gyu Pak; Un-Hui Kye; Jong-Sik Kim; Kwon-Mu Kim; Yong-Nam Sim; Je-Un Pak; Ki-Ung Song; et al. (Agroforestry Systems, 2012)

Large-scale sequencing of normalized full-length cDNA library of soybean seed at different developmental stages and analysis of the gene expression profiles based on ESTs - Ai-Hua Sha; Chen Li; Xiao-Hong Yan; Zhi-Hui Shan; Xin-An Zhou; Mu-Lan Jiang; Han Mao; Bo Chen; Xia Wan; Wen-Hui Wei (Molecular Biology Reports, 2012)

Regulation of auxin response by miR393-targeted transport inhibitor response protein 1 is involved in normal development in Arabidopsis - Zhe-Hao Chen; Mao-Lin Bao; Yu-Zhe Sun; Yan-Jun Yang; Xiao-Hong Xu; Jun-Hui Wang; Ning Han; Hong-Wu Bian; Mu-Yuan Zhu (Plant Molecular Biology, 2011)

The genetic profiling of preferentially expressed genes in murine splenic CD8α+ dendritic cells - Tao Li; Wu-Ying Li; Hui-Ling Bai; Hong-Bing Ma; Hu Zhang; Jiang-Mu Zhu; Xiao-Hong Li; Hong-Ying Huang; Yuan-Fang Ma; Xin-Ying Ji (Immunologic Research, 2011)

Combination of Hyaluronic Acid Hydrogel Scaffold and PLGA Microspheres for Supporting Survival of Neural Stem Cells - Ying Wang; Yue Teng Wei; Zhao Hui Zu; Rong Kai Ju; Mu Yao Guo; Xiu Mei Wang; Qun Yuan Xu; Fu Zhai Cui (Pharmaceutical Research, 2011)

Effects of temperature and initial pH on biohydrogen production from food-processing wastewater using anaerobic mixed cultures - Yen-Hui Lin; Mu-Ling Juan; Hsin-Jung Hsien (Biodegradation, 2011)

Alternative splicing of the antitrypsin gene in the silkworm, Bombyx mori - Hui-fen Liu; Yi-nü Li; Ru Jia; Wei-zheng Cui; Zhi-mei Mu; Zhi-fang Zhang (Molecular Biology Reports, 2011)

Polyclonal rabbit anti-murine plasmacytoma cell globulins induce myeloma cells apoptosis and inhibit tumour growth in mice - Bo Mu; Jin-liang Yang; Lan-tu Gou; Yu-qin Yao; Yan Zhou; Zhi-hui Cheng; Hua-shan Shi; Zhi-yong Li; Yuan Wen; Fei Leng; Feng-yu Cui; Tian-tai Ma; et al. (Apoptosis, 2011)

A novel genetic locus for familial febrile seizures and epilepsy on chromosome 3q26.2–q26.33 - Xiao-Hua Dai; Wen-Wu Chen; Xu Wang; Qi-Hui Zhu; Cong Li; Lin Li; Mu-Gen Liu; Qing-K. Wang; Jing-Yu Liu (Human Genetics, 2008)

Overexpression of the cucumber LEAFY homolog CFL and hormone treatments alter flower development in gloxinia (Sinningia speciosa) - Ming-Zhe Zhang; Dan Ye; Li-Lin Wang; Ji-Liang Pang; Yu-Hong Zhang; Ke Zheng; Hong-Wu Bian; Ning Han; Jian-Wei Pan; Jun-Hui Wang; Mu-Yuan Zhu (Plant Molecular Biology, 2008)

Phylogenetic Diversity of the Archaeal Community in a Continental High-Temperature, Water-Flooded Petroleum Reservoir - Hui Li; Shi-Zhong Yang; Bo-Zhong Mu (Current Microbiology, 2007)

Hypertonic saline resuscitation maintains a more balanced profile of T-lymphocyte subpopulations in a rat model of hemorrhagic shock - Yuan-qiang Lu; Xiu-jun Cai; Lin-hui Gu; Han-zhou Mu; Wei-dong Huang (Journal of Zhejiang University-SCIENCE B, 2007)

Applications of conditional nonlinear optimal perturbation in predictability study and sensitivity analysis of weather and climate - Mu Mu; Wansuo Duan; Hui Xu; Bo Wang (Advances in Atmospheric Sciences, 2006)

Molecular marker application in sugarcane - Mu-Qing Zhang; Xue-Fang Zheng; Ai-Li Yu; Jing-Sheng Xu; Hui Zhou (Sugar Tech, 2004)

Unfolding of titin domains studied by molecular dynamics simulations - Mu Gao; Hui Lu; Klaus Schulten (Journal of Muscle Research and Cell Motility, 2002)

Arnol'd Nonlinear Stability Theorems and their Application to the Atmosphere and Oceans - Mu Mu; Yong-Hui Wu (Surveys in Geophysics, 2001)